Improvement of Salt Tolerance in Maize by Exogenous Application of Proline (Journal of Environmental Science and Natural Resources, 2015)
Proline provides protection in plants against various abiotic stresses including salinity. The field experiment was conducted at the farmers field of coastal area (Botiaghata, Khulna) to mitigate the adverse effects of salinity on growth and yield of maize by exogenous application of proline. In the experiment maize plants were treated with different concentrations of proline at seedling and/or vegetative stages. The plant growth parameters, grain and stover yields, nutrient uptake and K+/Na+ ratio were recorded. All the yield contributing characters were significantly increased due to exogenous application of proline at different growth stages. Among the treatments, application of 100 mM proline at seedling and vegetative stages offered the highest grain and stover yields (5.7 t ha-1 and 9.8 t ha-1, respectively) of maize which was followed by 100 mM proline application at seedling stage where grain and stover yields were 5.7 t ha-1 and 9.7 t/ha, respectively. However no significant differences were found between two treatments. Total N, P and S uptake (203.66, 23.24 and 23.14 kg ha-1, respectively) were highest when the maize plants were treated with 100 mM proline at seedling and vegetative stages. The highest K+/Na+ ratio both in grain (12.92) and stover (5.57) was also observed in the same treatment. Therefore, it can be concluded that exogenous application of proline improves salinity tolerance in maize by increasing nutrient uptake and probably due to increasing antioxidant defense mechanisms.J. Environ. Sci. & Natural Resources, 8(1): 13-18 2015